The features of state changes of proteinase- inhibitory system in the lungs of guinea pigs in the early period of experimental bronchial asthma - M. S. Regeda; M. A. Kolishetska; N. G. Sementsiv; M. L. Baida (Journal of Education, Health and Sport, 2015)
Reheda M. S., Kolishetska M. A., Sementsiv N. G., Baida M. L. Особливості зрушень стану протеїназо-інгібіторної системи в легенях морських свинок у ранньому періоді експериментальної бронхіальної астми = The features of state changes of proteinase- inhibitory system in the lungs of guinea pigs in the early period of experimental bronchial asthma. Journal of Education, Health and Sport. 2015;5(11):419-426. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.34232